Particulate air pollution and neurological diseases: The role of tauopathies - Hsiao-Chi Chuang; Dean Wu; Jiunn-Horng Kang (Wolters Kluwer Medknow Publications, 2018)
Neurodegenerative diseases, such as dementia, Parkinson's disease, and parkinsonism, are due to the gradual and progressive loss of neural cells, leading to nervous system dysfunction. Increasing epidemiological and toxicological evidence has demonstrated the possible association between neurological diseases and particulate air pollution. Chronic exposure to particulate matter (PM) of < 2.5 μm in aerodynamic size (PM2.5) is related to reductions in white matter and gray matter in brains of older women. Alterations of the structural integrity of the brain were reported for particulate air pollution-induced neurological disorders. Clinically, intraneuronal accumulation of tau proteins is considered to be an important hallmark of the development of neurodegenerative diseases. In Alzheimer's disease brains, for example, hyperphosphorylated levels of tau are around 3-4 times higher than levels in normal adult brains. Tau overexpression in neuroblastoma cells can lead to tau aggregations and the appearance of smaller proteolytic fragments. Degradative mechanisms, such as autophagy that remove tau from cells are considered essential functions for maintaining the brain's health. Notably, increasing numbers of reports have indicated that autophagy dysfunction occurs due to particulate air pollution in vitro and in vivo. Dysfunction of autophagy can lead to tau accumulation in the brain. We reviewed the effects of particulate air pollution on neurological diseases and the underlying mechanisms (i.e., tau and autophagy). Further toxicological evidence is required to fill in the gaps between epidemiological and clinical observations.